PENINGKATAN KEKERASAN PERMUKAAN FERRO CASTING DUCTILE (FCD) 700 MELALUI PROSES NITRIDASI DENGAN MEDIA UREA - Wiwik Purwadi; Dewi Idamayanti; Firman (CR JOURNAL (CREATIVE RESEARCH FOR WEST JAVA DEVELOPMENT), 2015)
Ferro Casting Ductile (FCD) 700 is widely used for products requiring strength, ductility and impact resistance such as crank shaft. Surface hardening can be aplied to improve the performance of this material which can be accomplished through nitriding process. This research deals with nitriding process by using urea as the nitrogen source to achieve the surface hardness of 700 HV(600 HRC). Nitriding has been accomplished by varying the temperature (530oC, 550oC, 580oC, 600oC, and 620oC) and holding time (1-2hrs). The ratio between the amount of urea and surface area is constantly maintained at 0,25 g/mm2, while the room pressure in the nitriding tube was 0,3 Mpa. The hardness value and the microstructure are used to analyse the result. 1 hr of holding time with at the temperature of 580oC, 600oC, 620oC and 2 hrs holding time at 530oC, 550oC, 580oC, 600oC, dan 620oC has resulted white layer on the surface of the material. The maximum depth of white layer (4,83 μm) has been achieved at 2 hrs holding time and temperature of 620oC. The maximum hardness of 733 HV is resulted after holding the temperature at 580oC for 2 hrs.